Measurement of Social Innovation at Organisation’s Level: Theoretical Issues - Dainienė Rasa; Dagilienė Lina (Economics and Business)
The paper presents theoretical issues of social innovation measurement due to its multidimensional context. The purpose of this paper is to review the theoretical background on the topic of social innovation concept and TBL approach and to propose the conceptual model for measuring the value of social innovation at an organisation’s level.